1993
DOI: 10.1021/ja00075a008
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and kinetic evaluation of high-affinity FKBP ligands and the X-ray crystal structures of their complexes with FKBP12

Abstract: The design and synthesis of high-affinity FKBP 12 ligands is described. These compounds potently inhibit the m-rrans-peptidylprolyl isomerase (rotamase) activity catalyzed by FKBP 12 with inhibition constants (Ki,app) as low as 1 nM, yet they possess remarkable structural simplicity relative to FK506 and rapamycin, from which they are conceptually derived. The atomic structures of three FKBP12-ligand complexes and of one unbound ligand were determined by X-ray crystallography and are compared to the FKBP12-FK5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
312
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(326 citation statements)
references
References 11 publications
12
312
0
1
Order By: Relevance
“…Both molecules are capable of simultaneously binding to FKBP and the Fyn SH2 domain. The pYEEI peptide was linked covalently to two FKBP ligands, FK506 and SLF (15), to provide the desired bifunctional molecules, FKpYEEI and SLFpYEEI (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both molecules are capable of simultaneously binding to FKBP and the Fyn SH2 domain. The pYEEI peptide was linked covalently to two FKBP ligands, FK506 and SLF (15), to provide the desired bifunctional molecules, FKpYEEI and SLFpYEEI (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…SLF is smaller than FK506 and does not project as far from the FKBP protein surface. By using the three-dimensional structures of FKBP12 (15,18), FKBP52 (19), and the Fyn SH2 domain (20), the linkers between the two halves of the bifunctional molecules were designed to bring the FKBP surface into close proximity to the SH2 domain surface. The affinities of FKpYEEI and SLFpYEEI for recombinant FKBP12, FKBP52, and the Fyn SH2 domain were measured by using isothermal titration calorimetry (ITC, Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to find novel inhibitors of Mip, two previously reported pipecoline ring containing inhibitors A and B with K i (app) of 10 nM and 0.23 µM, respectively, were used as lead structures. While structure A contained the keto amide moiety, in structure B this group was replaced by a sulfonamide anchor (Holt et al, 1993(Holt et al, , 1994. Molecular docking studies revealed that structure A fitted less well to Mip than to the human homolog FKBP12.…”
Section: Pipecolinic Acid Derivativesmentioning
confidence: 99%
“…This compound binds to FKBP but, unlike rapamycin, does not possess affinity for FRB (Holt et al, 1993); thus, it can be used to compete for binding to FKBP and, perhaps, accelerate dissociation of the ternary FKBP-rapamycin-FRB complex. To test whether this competitor can influence the kinetics of protein localization, SLF (10 µM) was added to the culture medium after removal of rapamycin-containing medium.…”
Section: Reversibility Of Drug-based Nuclear Import and Exportmentioning
confidence: 99%